ReConNet: A Tool for Modeling and Simulating with Reconfigurable Place/Transition Nets - Padberg, Julia; Ede, Marvin; Oelker, Gerhard; Hoffmann, Kathrin (Electronic Communications of the EASST, 2012)
In this contribution we present a tool for modeling and simulation with reconfigurable Petri nets. Taking the idea of algebraic graph transformations to marked Petri nets we obtain Petri nets whose net structure can be changed dynamically. The rule-based change of the net structure enables the adequate modeling of complex, dynamic structures as for example of  the scenarios of the Living Place Hamburg. The tool \reconnet \ uses decorated  place/transition nets that are extended by various annotations. Especially, they  have transition labels that may change when the transition fires. The  transformation approach is based on the well-known algebraic transformation approach, but here we use a variant, namely the cospan approach, that inverts the relation between  left- and right-hand sides and interface in the  rules.